Improving Photocatalytic Activities of LaFeO3 Photocathode by Chromium-Incorporated Nanoparticle - Aadenan A.; Arzaee N.A.; Noh M.F.M.; Daud M.N.M.; Hisham D.H.B.; Anuar M.A.M.; Mustapha M.; Mohamed N.A.; Ahmad M.H.; Ibrahim M.A.; Ludin N.A.; Teridi M.A.M. (Korean Institute of Metals and Materials, 2025)
Incorporation of chromium (Cr) nanoparticle onto LaFeO3 (LFO) photocathode to improve optical and photocatalytic activities have been successfully demonstrated. The plain LFO photocathode was prepared by spin-spray gun deposition, following the Cr-incorporated nanoparticle onto the photocathode by spin coating method. It is observed that the photocathode with the optimal composition of 1.5 mmol Cr nanoparticle enhanced the crystal growth of orthorhombic crystal structure predominantly on (121) orientation with the formation of well-connected crystal grain architecture. The structure demonstrated strong optical absorption and a high current density of -60.52 A cm? 2 at -0.5V (vs. Ag/AgCl) more than twice to the untreated LFO film which recorded a maximum photocurrent of -21.83 A cm? 2 at -0.5V (vs. Ag/AgCl). This subsequently led to suppressed surface recombination, lower charge resistance and good stability in the strong alkaline electrolyte. The enhancement provided that incorporating a transition metal element with plain LFO would be applicable for producing efficient photosensitive devices, particularly for photoelectrochemical (PEC) water splitting applications. Graphical Abstract: (Figure presented.) ? The Author(s) under exclusive licence to The Korean Institute of Metals and Materials 2024.